PENGARUH PEMBERIAN BUBUR INSTAN MORPHALUS (TEPUNG DAUN KELOR, TEPUNG KACANG MERAH, TEPUNG IKAN GABUS) TERHADAP PENINGKATAN BERAT BADAN BAYI GIZI KURANG USIA 6-11 BULAN DI PUSKESMAS TAMAN BACAAN PALEMBANG - Podojoyo, Podojoyo; Siregar, Afriyana; Martini, Dina (Poltekkes Kemenkes Palembang, 2022)
Background: Undernutrition is still a major nutritional problem in Indonesia. Babies are one of the vulnerable groups experiencing nutritional problems. The direct cause of the occurrence of malnutrition is one of which is influenced by the intake of nutrients. Low energy, protein and fat intake causes optimal utilization of nutrients and susceptible to infectious diseases (Diniyyah, 2017). Therefore, with the provision of morphalus instant porridge that is high in energy and protein can help increase weight. Method: This research is a quasi-eskperimen study with a pre-test research design and post test with control group design. The study was conducted from January-March 2022. The sample number of 20 treatment respondents and 20 comparison respondents were carried out by purposive sampling. Results: Based on statistical tests in the treatment group and comparison group obtained the value of the baby's weight before and after the intervention with a p-value (<0.05) Conclusion: Morphalus instant porridge has an effect on increasing the weight of malnourished infants aged 6-11 months in the Working Area of ​​the Taman Bacaan Palembang Health Center Keywords: Undernutrition, Complementary food